PERBANDINGAN PENILAIAN AKHIR PEMBELAJARAN MATEMATIKA BERDASARKAN PENERAPAN KURIKULUM 2013 DAN KURIKULUM MERDEKA - Azizah Rizqi Mubarokah; Dori Lukman Hakim (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Curriculum updates in Indonesia have become part of the history of the development of this country's education which is the focus of discussion in this article. These changes include various aspects such as knowledge and assessment results obtained during the learning process so that there are many changes in the learning process which affect the adaptation system of students' learning processes. The aim of this research is to evaluate the implementation of learning between the 2013 curriculum and the independent curriculum on students' mathematics learning outcomes. The method used in this article is descriptive quantitative with the research subject involving the deputy principal or curriculum department and mathematics subject teacher at a private high school in the Karawang area. So the results of the analysis that have been carried out are the learning outcomes of students when using the 2013 curriculum and the independent curriculum, with an average number of 89.72 for the 2013 curriculum which is higher, while independent curriculum learning has an average number of 82.921 using the independent curriculum which is still in the early stages of implementation at school.